2017
DOI: 10.1080/21691401.2017.1307212
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of insulin-like growth factor 1 receptor specific siRNA and doxorubicin using chitosan-based nanoparticles enhanced anticancer efficacy in A549 lung cancer cell line

Abstract: Here, we investigated the effects of dual delivery of IGF-1R siRNA and doxorubicin by chitosan nanoparticles on viability of A549 lung cancer cells line by utilization of MTT and qRT-PCR. Furthermore apoptosis and migration of treated cells were assessed by Annexin-PI and wound healing assays, respectively. The chitosan nanoparticles had about 176 nm size with zeta potential and polydispersive index about 11 mV and 0.3, respectively. The IGF-1R siRNA had synergistic effect on DOX-induced cytotoxicity and apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…For evaluating cellular apoptosis, after seeding and treating with different concentrations of Ala, the HepG2 cells were collected into tubes and were suspended in DPBS. Briefly, for apoptosis assay, Annexin V-FITC/PI Apoptosis Detection Kit (KeyGEN BioTECH, Jiangsu, China) was used for flow cytometry as described earlier [20]. Apoptosis and necrotic cells were analyzed by a FACStar flow cytometer using the FlowJo version 7.6 software (FlowJo LLC, Ashland, OR, USA) and a minimum of 10,000 events was recorded for each sample.…”
Section: Dapi Staining and Flow Cytometry For Cellular Apoptosis Assaymentioning
confidence: 99%
“…For evaluating cellular apoptosis, after seeding and treating with different concentrations of Ala, the HepG2 cells were collected into tubes and were suspended in DPBS. Briefly, for apoptosis assay, Annexin V-FITC/PI Apoptosis Detection Kit (KeyGEN BioTECH, Jiangsu, China) was used for flow cytometry as described earlier [20]. Apoptosis and necrotic cells were analyzed by a FACStar flow cytometer using the FlowJo version 7.6 software (FlowJo LLC, Ashland, OR, USA) and a minimum of 10,000 events was recorded for each sample.…”
Section: Dapi Staining and Flow Cytometry For Cellular Apoptosis Assaymentioning
confidence: 99%
“…Reduced chances of side effects could decrease cytotoxicity, a high degree of specificity and efficacy, augment safety and potency, and also enhance stability/versatility. The possibilities of more easily and less expensively synthesizing are also advantages of Small interfering RNA (siRNA) usage (34)(35)(36)(37). Besides these, a combination of siRNA with chemotherapy shows more advantages, such as the capability of protein expression haltering with high sequence selectivity before translation instead of sequestering protein, like targeted therapy agents (38).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is possible that one protein via two distinct pathways could result in drug resistance. IGF1R is a member of the tyrosine kinase family (RTK) family that consists of two A and two B subunits with the free DOX or other groups (34) (Fig.2). HMGA2 belongs to high mobility group AThook proteins that by changing chromatin structure and interaction with various transcription factors plays a significant role in several biological processes, such as differentiation, EMT, apoptosis, invasion and cell growth (117,118).…”
Section: -3-simultaneous Drug Application and Gene Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Shali et al prepared a co-delivery system consisting of chitosan nanoparticles loaded with IGF-1 R siRNA and DOX to investigate their effects on the viability of A549 lung cancer cells line. The results showed that migration and expressions of mmp9, VEGF and signal transducer and activator of transcription 3 (STAT3) could be decreased in A549 cells, which could be useful in preventing the metastatic spread and in improving the treatment of lung cancer [48].…”
Section: Chitosan (Cs)-based Npsmentioning
confidence: 99%